An Analysis of the Relation between One's Worldview and Sexual affairs and Chastity in the cinema; Case Study of Sausages Party Animation - Mohammad Majid Shahbazi; Mohammad Amin Behzadnasab; Mohammad Reza Borzouee (Religion & Communication, 2019)
In today's information age our individual lives are combined with the media, hence one of the most attractive amusements is watching animations. In recent decades, 3D animations, due to their unique technical specifications, attractiveness, and offering suitable grounds for transmitting diverse contents, have appealed to a vast number of people at different age levels. What counts here is the efforts made to provide educational products side by side with entertainment. Meanwhile, some included immoral contents have threatened the society's norms of modesty. This research has extracted some messages from the 3D Sausage Party animation (2016) produced by Hollywood's Columbia Pictures and analyzed it with an educational approach and use of quality content analysis. The obtained concepts led to the development of a duality at three levels, namely worldview, beliefs, and behaviors. Finally, a model is presented that shows each worldview can create its own sexual beliefs and consequently its unique chaste behavior in sexual domains.